Protocol for in vivo chromatin immunoprecipitation on purified chromatin isolated from mouse liver nuclei - Lei Li; May G. Akl; Scott B. Widenmaier (STAR Protocols)
Summary: Chromatin immunoprecipitation (ChIP) is used to investigate genome binding by transcription factors, but it can be problematic. We present a protocol to isolate fixed DNA-protein complexes from mouse liver prior to chromatin shearing. We describe steps for liver disaggregation and cross-linking, DNA-protein complex isolation, chromatin shearing, and quality control analysis as well as procedures for ChIP, DNA purification, and ChIP analysis. This protocol yields high-quality samples using commercial antibodies.For complete details on the use and execution of this protocol, please refer to Akl et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.